The rhetorical blue economy in Bangladesh: Analyzing the inborn regulatory bottlenecks - Rahman, Md. Mizanur (Universitas Malikussaleh, 2021)
This study's overreaching objective was to assess the suitability and applicability of the existing legal and institutional framework for managing the coastal and marine resources in Bangladesh. Together with, the fundamental challenges faced by the artisanal and small-scale fishers in Bangladesh were critically scrutinized. The study revealed that the regulatory framework in Bangladesh is characterized by jurisdictional overlapping followed by the conflict of interests among the public institutes, which originated from the aged and fragmented laws and ambiguous business allocation; consequently, the artisanal and small-scale fishers suffer a lot. The local government and community's right to resource management remains fuzzy. Bangladesh can enact new sectoral laws followed by business reallocation for the line ministries. The study will help policymakers identify the bottlenecks rooted in the existing regulatory and institutional framework.Keywords: Coastal and Marine Resource; Jurisdictional Overlapping; Conflict of Interests; Marine Governance; Artisanal Fishers